ANALISIS PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, LEVERAGE, DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN - Rosalia, Santi; Adhi, Daniel Kartika; Mohklas, Mohklas (STIE PENA, 2024)
This research aims to find out whether company size, company age, leverage and liquidity have an effect on financial performance. Population in this study is food and beverage companies listed on the IDX in 2021–2023. Determining the sample in this study used a purposive sampling method, based on criteria determined by the number of samples collected as many as 35 companies. This research uses descriptive analysis and hypothesis testing using SPSS. The type of data used is secondary data. The test techniques used are classical assumption tests, multiple regression tests and hypothesis tests. Results of this research show that company size and leverage do not have a negative and significant effect on financial performance, company age does not have a positive and significant effect on financial performance, while liquidity has a positive and significant effect on financial performance. Keywords: Company Size, Company Age, Leverage, Likuidity, and Financial Performance